Natural Mosquito Repellet Socialization for Dengue Prevention in Rural Areas: Sosialisasi Semprotan Anti Nyamuk Alami untuk Pencegahan Demama Berrdarah - M Zufar Irhab S Putra; Sekar Arum Melati; Dinda Putri Arnindi; Desy Miftachul Ilmi Arifin Putri; Trimono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Dengue fever remains a significant public health concern, necessitating comprehensive prevention strategies, including vector control. This community engagement study explores the implementation of natural mosquito repellent spray production using lemongrass as a strategic approach to mitigate dengue transmission in Lontar Village. The research aims to analyze the impact of this natural repellent on community health, identifying challenges and opportunities associated with its adoption and sustainable production. Employing a mixed-methods approach, the study incorporates community surveys, interviews with local residents and health officials, and direct observation during the socialization and production phases. Findings indicate that the provision of natural mosquito repellent significantly enhances community participation in dengue prevention, offering an accessible and environmentally friendly alternative to chemical repellents. Key challenges include initial awareness dissemination regarding the benefits of natural repllents and ensuring consistent home-based production. However, the benefits demonstrate substantial potential for improving local health outcomes, fostering self-reliance in disease prevention, and promoting the use of local resources. The study suggests targeted support mechanisms, including continuous education, hands-on workshops, and simplified production guidelines to maximize the benefits of this natural repellent. These findings contribute to understanding the role of community-based interventions in local health development and provide practical insights for supporting disease prevention efforts in rural contexts. The research highlights the importance of strategic interventions that can empower communities to adopt sustainable health practices.